2017
DOI: 10.1038/boneres.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosignaling activation of TGFβ maintains intervertebral disc homeostasis

Abstract: Intervertebral disc (IVD) degeneration is the leading cause of disability with no disease-modifying treatment. IVD degeneration is associated with instable mechanical loading in the spine, but little is known about how mechanical stress regulates nucleus notochordal (NC) cells to maintain IVD homeostasis. Here we report that mechanical stress can result in excessive integrin αvβ6-mediated activation of transforming growth factor beta (TGFβ), decreased NC cell vacuoles, and increased matrix proteoglycan product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 68 publications
(81 reference statements)
4
92
0
2
Order By: Relevance
“…These alternations can cause a deficiency in important cellular defense mechanisms, which contributes to the initiation and progression of tissue damage [15, 16]. Recently, such dysfunction of intervertebral disc homeostasis has been proposed as one of the main mechanisms in IDD [17-19]. In particular, the activation of AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling has been demonstrated to mediate these defective intracellular functions [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…These alternations can cause a deficiency in important cellular defense mechanisms, which contributes to the initiation and progression of tissue damage [15, 16]. Recently, such dysfunction of intervertebral disc homeostasis has been proposed as one of the main mechanisms in IDD [17-19]. In particular, the activation of AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling has been demonstrated to mediate these defective intracellular functions [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its adverse impulsion on either individuals or society, IDD has been a highlighted research field, and many factors have been found to contribute to the development of IDD, including age, metabolism, nutrition, and mechanical loading [37]. Among those damaging factors, excessive/abnormal mechanical loading on IVD has been determined to be a primary incentive [38].…”
Section: Discussionmentioning
confidence: 99%
“…Among those damaging factors, excessive/abnormal mechanical loading on IVD has been determined to be a primary incentive [38]. Moreover, the underlying mechanism of pressure-induced IDD has now been clarified to a great extent, and many singling pathways have been demonstrated to be involved in the progress, such as TGF-β, PI3K/Akt pathway, and p38-MAPK pathway [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological homeostasis of NP tissue relies on the balance of ECM, which is determined by anabolic and catabolic activities. 36 As the disk degenerates, cell properties of NPCs, responsible for producing NP extracellular matrix components such as proteoglycans and collagens, are inhibited accordingly. 37 The inflammatory cytokine TNF-a significantly suppresses ECM gene expression and promotes expression of ECM-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%